Identifikasi dan Penilaian Risiko Keselamatan dan Kesehatan Kerja pada Gedung Teknik Kimia - Slafudin; Sirotun Nazwa; Steavany Sari Pratiwi; Riny Yolandha Parapat (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Occupational Health and Safety (OHS) is an important aspect in creating a safe, healthy, and productive working environment, including in Chemical Engineering buildings that have various potential hazards due to laboratory activities, the use of chemicals, and the operation of laboratory equipment. This study aims to identify potential OHS risks, assess the level of risk, and determine risk control measures in the Chemical Engineering building. The method used was Hazard Identification and Risk Assessment (HIRA), which includes hazard identification, risk assessment based on the likelihood and severity levels, and the implementation of risk control according to the hierarchy of controls. The results showed that several potential hazards identified included chemical exposure, fire hazards, gas leakage, electrical hazards, and work accidents caused by the use of laboratory equipment. The risk levels obtained were categorized as low, medium, and high depending on the type of activity and the working environment conditions. Risk control measures were carried out through hazard elimination, material substitution, engineering controls, administrative controls, and the use of personal protective equipment (PPE). In addition, the implementation of OHS training, safety induction, and periodic evaluations are important steps in improving the safety culture within the Chemical Engineering building environment. With the implementation of a proper OHS system, it is expected that the risk of work accidents can be minimized, thereby creating a safe and comfortable learning and working environment.